2019
DOI: 10.3390/v11060565
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Reassortant Highly Pathogenic Avian Influenza (H5N2) Virus in Egypt

Abstract: Highly pathogenic avian influenza (HPAI) H5N1 and H5N8 have become endemic among domestic poultry in Egypt since 2006 and 2016, respectively. In parallel, the low pathogenic avian influenza H9N2 virus has been endemic since 2010. Despite the continuous circulation of these subtypes for several years, no natural reassortant has been detected so far among the domestic poultry population in Egypt. In this study, the HPAI (H5N2) virus was isolated from a commercial duck farm, giving evidence of the emergence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Although no A(H5N1)/A(H9N2) reassortants have been described, a novel A(H5N8)/A(H5N1) reassortant has been detected in a duck. This virus contained seven A(H5N8) virus genes with the N2 from the A(H9N2) virus (Hagag et al 2019). The complete significance of this or similar viruses remains unknown.…”
Section: Reassortment Of Hpaiv H5nx In Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no A(H5N1)/A(H9N2) reassortants have been described, a novel A(H5N8)/A(H5N1) reassortant has been detected in a duck. This virus contained seven A(H5N8) virus genes with the N2 from the A(H9N2) virus (Hagag et al 2019). The complete significance of this or similar viruses remains unknown.…”
Section: Reassortment Of Hpaiv H5nx In Egyptmentioning
confidence: 99%
“…In the second event, there was another introduction(s) of Gs/GD A(H5) viruses from Asia, this time of clade 2.3.4.4 A(H5N8) viruses Salaheldin et al 2018a). These viruses have slowly displaced clade 2.2 viruses and have not been detected in humans, but reassortment with circulating A(H9N2) viruses has been observed (Hagag et al 2019) (see below for more details).…”
mentioning
confidence: 99%
“…Furthermore, the Asian lineage HPAI A(H5N2) was for the first time detected in wild birds; a grey heron (Ardea cinerea) found dead in Guandu Park in Taipei City. The (Hagag et al, 2019). Phylogenetic analysis showed that the virus had emerged as a result of reassortment between A(H5N8) clade 2.3.4.4B and A(H9N2) viruses of the G1 lineage, endemically circulating in the country since 2011.…”
Section: Detectionsmentioning
confidence: 99%
“…comm.) in the country may represent a diagnostic challenge, considering that new reassortant viruses could emerge, as recently reported in Egypt [13,14], and spread. Urgent actions to strengthen surveillance efforts, combined with eradication measures, adequate compensations and education of farmers are needed to contain and monitor virus spread and the emergence of novel viruses of animal and public health concern.…”
mentioning
confidence: 95%